Local Wisdom in Kaba Bonsu Pinang Sibaribuik By Emral Djamal Dt. Rajo Mudo: a Heuristic- Hermeneutic Review - Fikri, Hasnul (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe four forms of local wisdom found in Kaba Bonsu Pinang Sibaribuik (KBPS) by Emral Djamal Dt. Rajo Mudo. The four forms of local wisdom are (a) philosophy, (b) a social attitude of life, counsel and the message, (c) traditional ceremonies, and (d) habits or behaviour in social intercourse. The method of this research is qualitative descriptive. The data of this research are words, sentences, and discourses that contain local wisdom in KBPS. Four critical findings of this research are observed. First, local wisdom based on observation are self- esteem, logical reasoning, optimistic, and strong attitude. Secondly, local wisdom based on social attitude is communalism and egalitarian, cooperating, caring, generous and helpful. Third, local wisdom based on ceremony or traditional ceremonies are alua (procedure, way) and patuik (proper), regulation about the procedure and place of discussion, and role of bundo kanduang (queen mother). Fourth, local wisdom based on habits or daily behaviour in social intercourse is prioritizing agreement, putting forward ethics and attitudes, rukun (peaceful), saiyo-sakato (agreement), equality and togetherness, mutual respect and caring, democratic attitude of listening, and unselfishness. It’s can concluded that KBPS is a useful source to recognize and understand the local wisdom of the Minangkabau community so it needs to be studied and preserved.